2016
DOI: 10.1111/tbed.12512
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bluetongue Virus 24 from India - An Exotic Serotype to Australasia

Abstract: Bluetongue (BT) is a viral disease of ruminants and is caused by different serotypes of bluetongue virus (BTV), which is transmitted by several species of Culicoides midges. The disease is endemic in tropical areas, and incursions have been observed in some of the temperate areas. Twenty-seven recognized serotypes of BTV have been reported so far. Some serotype viruses have been shown to circulate in certain geographical areas. BTV-24 has been reported from Africa, the Mediterranean and the Americas, whereas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 20 publications
(28 reference statements)
1
25
0
Order By: Relevance
“…, ; Krishnajyothi et al . ). This will remove the potential shortcomings that can result from a primary reliance on serological BTV characterization of epitopes present on the gene product of Seg‐2 alone.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…, ; Krishnajyothi et al . ). This will remove the potential shortcomings that can result from a primary reliance on serological BTV characterization of epitopes present on the gene product of Seg‐2 alone.…”
Section: Discussionmentioning
confidence: 97%
“…Thus within the context of the total gene constellation currently present in the Northern Australian BTV episystem, co-segregation of Seg-2, -5 and -7 may be necessary for the preservation of essential outer core structural interdependence between their respective expression products, at least for BTV-5 and BTV-7. Speculation on how rapid BTV gene segment translocations between Western and Eastern episystems might occur has included trade in live animals, semen and embryos (Mintiens et al 2008;Rao et al 2012a;Krishnajyothi et al 2016), live vaccine use and importation of vaccinated animals (Maan et al 2015). Sequential vector species expansion events due to extraordinary climatic conditions and long distance wind dispersals, causing overlap with and allowing novel BTV gene incursions into neighbouring episystems, are also thought to play a major role (Hendrickx 2009;Eagles et al 2012Eagles et al , 2013Eagles et al , 2014Purse et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples from sheep showing BT‐like symptoms were collected from several outbreaks from different parts of Andhra Pradesh and Telangana states in South India, and virus isolation was accomplished by passaging the RBC lysates in KC cells followed by BHK‐21 cells. All the isolates ( n = 108) were tested by RT–PCR with primers against eight serotypes of BTV (BTV‐1, BTV‐2, BTV‐9, BTV‐12, BTV‐16, BTV‐21, BTV‐23, BTV‐24) circulating in India during the last decade (Krishnajyothi et al., ; Reddy et al., ). Sequence generated from one of the previously untyped virus isolates using next‐generation sequencing platform revealed that the isolate was related to BTV‐4 (Acc.…”
Section: Resultsmentioning
confidence: 99%
“…In the Indian context, emergence of nephropathogenic avian infectious bronchitis virus (Bayry et al, 2005), porcine circovirus2 (Karuppannan et al, 2016), re-emerging BTV serotypes (Hemadri et al, 2016;Krishnajyothi et al, 2016;Rao et al, 2016), avian influenza (Bhat et al, 2017;Nagarajan et al, 2017) and new variants of foot and mouth disease virus (Mahapatra et al, 2016;Rudreshappa et al, 2012;Yuvaraj et al, 2013), and porcine respiratory and reproductive syndrome virus (PRRSV) (Rajkhowa et al, 2015) are some examples where NGS would have helped.…”
Section: Diagnosis Of Infectious Diseases and Monitoring Of Outbreaksmentioning
confidence: 99%